Some Approach in Assessing Information Technology Policies in Our Mining Industry under the Impact of the Industrial Revolution 4.0 (Case study: Vietnam National Coal and Mineral Industries Group – Vinacomin) - Thi Hai Van, Tran; Minh Quan, Doan (VNU Journal of Science: Policy and Management Studies; Vol 37 No 1DO - 10.25073/2588-1116/vnupam.4279, 2021)
Since 1997, the mining industry has paid attention to develop information-technology (IT) components at sectoral and enterprise levels. However, due to various reasons, including the interest of business and sector leaders as well as limited resources, IT in the mining industry is still on a small scale, in which it has not yet linked to a network and had a shared database, and is therefore not shared. Under the impact of Industry Revolution 4.0, to develop the IT field as an essential tool to promote the technologies of the 4.0 technology component, a systematic policy combination is needed. This article is responsible for meeting that demand of the IT field of Vietnam's mining industry. Keywords Industry 4.0, IT, IT policy. References [1] K. Schwab, The Fourth Industrial Revolution: What It Means and How to Respond, https://www.weforum.org/agenda/2016/01/the-fourth-industrial-revolution-what-it-means-and-how-to-respond/, 2015. [2] Forschungsunion, Acatech, Recommendations for implementing the strategic initiative INDUSTRIE 4.0, Final report of the Industrie 4.0 Working Group, April 2013. [3] J.H. Leavitt, L.T. Whisler, Management in the 1980’s, Harvard Business Review, 1958-11. [4] National Assembly of Vietnam, Law on information technology (No. 67/2006/QH11), June 29, 2006 (in Vietnamese). [5] National Association directing the compilation of encyclopedias (Vietnam), Vietnamese encyclopedia, Hanoi, Vietnam, 1995 (in Vietnamese), [6] Wikipedia, Thomas Kuhn, https://vi.wikipedia.org/wiki/Thomas_Kuhn, 2019. [7] V.C. Dam, Scientific research methodology Science and Technics Publishing House, Hanoi, Vietnam, 1999 (in Vietnamese).